2020
DOI: 10.1093/jnci/djaa206
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Epigenetic Aging of the Right vs Left Colon

Abstract: There are well-documented racial differences in age-of-onset and laterality of colorectal cancer. Epigenetic age acceleration is postulated to be an underlying factor. However, comparative studies of side-specific colonic tissue epigenetic aging are lacking. Here, we performed DNA methylation analysis of matched right and left biopsies of normal colon from 128 individuals. Among African Americans (n = 88), the right colon showed accelerated epigenetic aging as compared to individual-matched left colon (1.51 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
0
27
0
2
Order By: Relevance
“…Because genome-wide DNA methylation studies show shared epigenomic features between aging and cancer, providing explanations for their possible molecular links [ 12 , 13 , 14 ], the role for DNAm age in carcinogenesis has been recently explored. The obtained results indeed indicate that DNAmaa increases cancer risk, promote cancer initiation or progression, and predict poor patient outcomes in different types of cancer [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, in some other cancers, DNAmad is associated with aggressive diseases and shorter survival.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Because genome-wide DNA methylation studies show shared epigenomic features between aging and cancer, providing explanations for their possible molecular links [ 12 , 13 , 14 ], the role for DNAm age in carcinogenesis has been recently explored. The obtained results indeed indicate that DNAmaa increases cancer risk, promote cancer initiation or progression, and predict poor patient outcomes in different types of cancer [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, in some other cancers, DNAmad is associated with aggressive diseases and shorter survival.…”
Section: Introductionmentioning
confidence: 69%
“…Importantly, the accelerated DNAm age in normal cells derived from healthy individuals is associated with increased cancer risk and cancer-related mortality [ 8 , 9 , 11 , 17 , 18 , 21 , 28 , 29 , 30 , 31 ]. Devall et al observed that higher DNAm age rates contributed to young age onset of colon cancer in African Americans [ 10 ]. Moreover, in patients with breast and colorectal cancer, their matched normal tissues frequently display significantly accelerated DNAm age [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported age acceleration (Horvath metric) in the right colons of African Americans and deceleration in the right colons of their European American peers. The authors stated, "our results provide novel insight of epigenetic aging potentially underlying racial disparities in CRC [26]." We recommend that future studies of epigenetic aging in CRC-and otherwise-continue to be mindful of suggesting that disparities are solely due to ancestry.…”
Section: Discussionmentioning
confidence: 93%
“…These changes may be accelerated via the production of bacterial metabolites [ 106 ], thus reflecting an individual’s gut microbiome and/or diet. The rate of DNA methylation also changes with age, and is reportedly side- and race-specific [ 107 ]. Accordingly, epigenetic markers may have greater utility for indicating potential pathways to CRC subtype formation [ 12 , 105 , 108 ] as opposed to being considered as a means to identify patients presenting in primary care who should be progressed for clinical investigation.…”
Section: Genetic Markersmentioning
confidence: 99%